Tourism and energy nexus in selected South Asian countries: a panel study. Issue 16 (17th August 2020) - Amin, Sakib B.; Kabir, Foqoruddin Al; Khan, Farhan
ABSTRACT: The main aim of this paper is to analyse the tourism-energy nexus for the selected South Asian countries by incorporating panel data set between 1995–2015. All the concerned variables are integrated at the first-differenced form and cointegrated in the long run. Dumitrescu-Hurlin panel non-granger causality test reveals a unidirectional causality from tourism to energy consumption in the long run, which further has a unidirectional causation effect on economic growth. Our results are expected to guide the policymakers to design appropriate policies for tourism and energy industries to promote sustainable growth in the South Asian countries.